EFFECTS OF ACUTE STRESS DURATION ON THE RAT BRAIN MAST CELL ACTIVATION - Paundralingga, Obed Trinurcahyo Kinantyo; Darkim, Darmawan; Munir, Badrul; Daeng, Bonaventura Handoko (Malang Neurology Journal, 2017)
Background. Stress of varying duration and types are known to affect the number and activation level ofÂ cerebral mast cells (MCs) via plasma CRH. Although MC number is known not to be increased in acuteÂ stress, elevated plasma CRH might still activate brain MCs.Objective. To investigate the effect of acute stress of incremental duration to the activation level ofÂ thalamic and hippocampal mast cells using elevated platform test to elicit stress in male Wistar rats.Methods. This research used randomized post-test only control group design with 4 control group of 30, 60, and 90 minute stress exposure. Mast cell activation of the regiotalamus and hippocampus is assessed by histomorphometrics.Results. In the hippocampus, we found a significant difference of MC activation between control and experimental groups (p=0.014; p<0.05) but not among the incremental duration of acute stress. However, MC activation was not different between control and experimental groups in the thalamus.Conclusion. Acute stress exposure increases MC activation without recruiting further MCs in specific cerebral region but the duration of acute stress itself does not affect the activation level.